2014
DOI: 10.1007/s00268-013-2442-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes in the Management of High‐Risk Incisional Hernias Utilizing Biological Mesh and Soft‐Tissue Reconstruction: A Single Center Experience

Abstract: This technique was associated with a low risk of surgical site occurrences and hernia recurrence, with no requirements for mesh explantation. Repair of such complex incisional hernias remains challenging, and further randomized controlled trials are required to elucidate the optimal method of closure and mesh type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
1
18
0
1
Order By: Relevance
“…Sixty-five articles described LOD in the context of ventral hernia patients, 9 articles described LOD caused by giant inguinal hernia, and 3 articles described giant diaphragmatic hernia. Sixty-seven articles were from the primary literature, comprising 44 case series, 17 case reports, 4 retrospective database analyses [ 18 , 33 35 ], and 2 retrospective interventional studies [ 36 ] [ 30 ]. Ten articles were from the secondary literature comprising seven editorials, two systematic reviews [ 20 , 37 ] and one consensus questionnaire [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-five articles described LOD in the context of ventral hernia patients, 9 articles described LOD caused by giant inguinal hernia, and 3 articles described giant diaphragmatic hernia. Sixty-seven articles were from the primary literature, comprising 44 case series, 17 case reports, 4 retrospective database analyses [ 18 , 33 35 ], and 2 retrospective interventional studies [ 36 ] [ 30 ]. Ten articles were from the secondary literature comprising seven editorials, two systematic reviews [ 20 , 37 ] and one consensus questionnaire [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biologic materials-based meshes (BIOMESH) have recently emerged as a useful option to repair VH in high-risk patients; these meshes in fact, carry a lower risk of infection and degrade in septic fields thus avoiding the necessity of removal [ 3 , 10 ]. Piazzese et al in 2004 demonstrated no differences in terms of wound complications and VH recurrence in liver-transplanted patients undergoing incisional hernia repair comparing synthetic mesh with biological mesh [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, reinforcement with a prosthesis is favorable [1] , and the Rives–Stoppa technique is thought to be the most standard open surgical procedure [2–4] The component separation technique is another effective procedure. Although it is insufficient without a prosthesis [5] , it may be very effective with the use of a prosthesis [6] . Finally, laparoscopic hernioplasty has also been developed and its use is increasing [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Candidates for incisional hernioplasty are usually patients with a high body mass index [3,4] and nonelderly patients [5,8] . Elderly patients with a small body size may also develop incisional hernias; however, most elderly patients with a thin abdominal wall do not undergo repair; instead, their hernia is simply observed.…”
Section: Introductionmentioning
confidence: 99%